Sea change: a sensemaking perspective on competing institutional logics - Moss Cowan, A (2013)
In recent years, institutional theorists have been increasingly interested in institutional change, seeking to understand the contextual factors and agents responsible for alterations to existing institutional arrangements. Institutional theory’s historical focus on isomorphism has made it challenging to account for actors’ motivations to pursue change projects. It is generally believed, though, that agents are mobilized through exposure to multiple institutional logics. Recently, scholars have begun to recognize that competition among multiple logics may not quickly produce a ‘winning logic’; rather, such logics may co-exist for prolonged periods in a context of ‘institutional complexity’. The turn toward institutional complexity reveals that preoccupation with the ‘paradox of embedded agency’ has left the development of change projects themselves under-theorized: What happens when organizational actors must interpret puzzling institutional contexts and generate alternatives? In seeking to understand organizational actors’ efforts to cope with conflicting logics in a context of scientific uncertainty, this study aligns with this growing interest in institutional complexity. Drawing on concepts from sensemaking theory, this research illuminates how actors with divergent interests, enacting their organizational roles, cope with competing logics and interact around a change project that emerges as a result of their efforts at coping. It thus contributes to institutionalist understandings of institutional complexity and change and adds to an emerging body of research linking institutional theory and sensemaking. The empirical setting for this single-case study is the ‘sustainable seafood’ discourse that began in the early 1990s when the cod collapsed off North America’s eastern seaboard. Prolonged scientific uncertainty regarding the collapse made generation of preferred alternatives problematic; this resulted in lengthy sensemaking efforts by multiple stakeholder groups, drawing on different institutional logics to produce divergent and competing interpretations and action scripts. Tracing the evolution of this discourse through documents, observations, and interviews empirically reveals processes of interrelated sensemaking, and further, exposes sensegivers as bricoleurs who use institutional elements creatively to affect the sensemaking of others.